2007
DOI: 10.1086/516709
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Loss and Retention on Kuiper Belt Objects

Abstract: Recent discoveries have shown that the very largest Kuiper Belt objects-Eris, 2005 FY9, and Sedna-are coated in methane and may contain other volatile ices as well. New detailed observations show that even within this class of volatile-rich bodies, unexpected differences exist in their surface compositions. 2005 FY9, a body approximately 60% the size of Pluto, with a reflectance spectrum similarly dominated by methane, has a surface depleted in molecular nitrogen by at least an order of magnitude with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
149
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 28 publications
4
149
1
Order By: Relevance
“…We nonetheless find a cluster of featureless objects among the red group of large objects: these might represent the most irradiated/oldest surfaces in the overall population. Therefore, it seems that a simple explanation such as the model of atmospheric escape proposed by Schaller & Brown (2007) might not be sufficient to explain the colors and compositions of KBOs. The reason why they evolved into two different color groups can be very complex, and should involve different thermal, collisional, irradiation histories, in addition to possibly different birthplaces.…”
Section: Discussionmentioning
confidence: 99%
“…We nonetheless find a cluster of featureless objects among the red group of large objects: these might represent the most irradiated/oldest surfaces in the overall population. Therefore, it seems that a simple explanation such as the model of atmospheric escape proposed by Schaller & Brown (2007) might not be sufficient to explain the colors and compositions of KBOs. The reason why they evolved into two different color groups can be very complex, and should involve different thermal, collisional, irradiation histories, in addition to possibly different birthplaces.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to Pluto and Triton which have spectra dominated by CH 4 , Quaoar's spectrum is dominated by H 2 O ice. The much reduced ability of Quaoar to retain very volatile species compared to Pluto and Triton (Schaller & Brown 2007a) could have led to a very different evolution with time of the surface volatiles, with the less volatile H 2 O ice being much more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of small amounts of CH 4 on Quaoar is not too surprising. Indeed, Schaller & Brown (2007a) have shown that, given its size and distance from the Sun, Quaoar could have retained at least some of the very volatile species like CH 4 , N 2 or CO that are observed on the surface of Pluto and other TNOs larger than Quaoar.…”
Section: Introductionmentioning
confidence: 99%
“…Schaller and Brown (2007a) have recently examined the volatile loss and retention on distant icy (Kuiper Belt) Solar System objects. They find that a ∼ 800 km object is able to retain its volatiles (N 2 , CH 4 , CO) over the age of the Solar System only if its "equivalent" temperature (essentially their perihelion temperature) is less than ∼ 30 K. Clearly, an equilibrium atmosphere of N 2 and CH 4 is not expected on Titania, consistent with the absence of features due to their ices in its near-infrared spectrum.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Licandro et al (2006b), Makemake formerly known as 2005 FY 9 (Licandro et al 2006a), and recently on Quaoar (Schaller and Brown 2007b), while the presence of N 2 on Eris is indirectly suggested (Licandro et al 2006b;Dumas et al 2007). At a current distance of 43 AU, and with its large size (1260 ± 190 km) which makes its ices marginally stable over the age of the Solar System (Schaller and Brown 2007a), Quaoar appears to be a promising occultation target for an atmosphere.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%